2002
DOI: 10.1101/gad.1016202
|View full text |Cite
|
Sign up to set email alerts
|

Nodal activity in the node governs left-right asymmetry

Abstract: Nodal is expressed at the lateral edges of the mouse node, but its function in this "organizer" tissue remains unknown due to the early lethality of Nodal mutant embryos. Here we used a genetic strategy to selectively remove Nodal activity from the node. Embryos lacking Nodal in the node fail to initiate molecular asymmetry in the left lateral plate mesoderm and exhibit multiple left-right patterning defects. Nodal may also act as a short-range signal to establish a functional midline barrier. Our findings con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
239
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(257 citation statements)
references
References 42 publications
16
239
0
Order By: Relevance
“…7C), in which Nodal protein synthesized in the bilateral PNC domain diffuses as a morphogen to the LPM (Nakamura et al, 2006, Ohi andWright, 2007). Rabbit LP explant cultures isolated before the onset of PNC Nodal transcription never initiated LPM Nodal (not shown), in agreement with corresponding genetic data in mouse (Brennan et al, 2002;Saijoh et al, 2003). In that setting, the role of an inhibitor on both sides falls upon FGF8, which acts to prevent the initiation of the autoregulatory Nodal feedback loop, in which Nodal signaling induces Nodal transcription (Saijoh et al, 2000;Hamada et al, 2002, Ohi andWright, 2007).…”
Section: Discussionsupporting
confidence: 82%
“…7C), in which Nodal protein synthesized in the bilateral PNC domain diffuses as a morphogen to the LPM (Nakamura et al, 2006, Ohi andWright, 2007). Rabbit LP explant cultures isolated before the onset of PNC Nodal transcription never initiated LPM Nodal (not shown), in agreement with corresponding genetic data in mouse (Brennan et al, 2002;Saijoh et al, 2003). In that setting, the role of an inhibitor on both sides falls upon FGF8, which acts to prevent the initiation of the autoregulatory Nodal feedback loop, in which Nodal signaling induces Nodal transcription (Saijoh et al, 2000;Hamada et al, 2002, Ohi andWright, 2007).…”
Section: Discussionsupporting
confidence: 82%
“…Genetic analyses have suggested that Nodal expression at the node is required for the activation of left-determinant transcription cascade in the left LPM (15,16). Our data, would suggest the molecular defect underlying the Megf8 m/m phenotype is either an interruption of signal transfer from the node to left LPM and/or a disruption in the initiation and expansion of Nodal expression in the LPM.…”
Section: Megf8 Morpholino Knockdown In Zebrafish Causes Heterotaxymentioning
confidence: 67%
“…In mice, L-R determination relies on Nodal expression at the periphery of the node, a specialized structure located immediately rostral to the primitive streak ( Fig. 2) (Brennan et al 2002). Nodal is initially expressed symmetrically along both the right and left side of the node, but a leftward flow generated by node cilia rotation (see below) causes enhanced Nodal signaling on the left node, eventually breaking the L-R symmetry by up-regulating Nodal expression in the left node and left LPM.…”
Section: Tail Bud Formation Somitogenesis and Left-right Determinationmentioning
confidence: 99%